Risk and Return Analysis of Bank Muamalat Indonesia Financing Using VaR and RAROC Methods - Ulul , Husna Rizky Tania; Manan, Abdul (Economics and Business Solutions Journal, 2025)
This research aims to measure the potential risk and potential return as well as the application of the high risk high return principle of murabahah, mudharabah and musyarakah financing at Bank Muamalat Indonesia for the 2019-2023 period. The calculation technique uses the VaR and RAROC methods. The results of the analysis show that murabahah financing has the smallest potential risk and mudharabah financing has the greatest potential risk. This can be seen from the magnitude of the VaR (Mean) and VaR (Zero) values. Throughout the year period the VaR value always shows a negative value, which means it shows the potential return. In line with VaR calculations, positive RAROC method calculation results indicate potential returns that are adjusted to have potential profits due to income received being greater than the value of expected losses. Meanwhile, the application of high return, high risk is not in accordance with the potential risk and return as measured by the RAROC method. The RAROC value which indicates the largest return is in 2022, while the equivalent rate which indicates the smallest return (biggest risk) is in 2019.